Aerosolized Intratracheal Inoculation of Recombinant Protective Antigen (rPA) Vaccine Provides Protection Against Inhalational Anthrax in B10.D2-Hc0 Mice - Song, Xiaolin; Zhang, Wei; Zhai, Lina; Guo, Jianshu; Zhao, Yue; Zhang, Lili; Hu, Lingfei; Xiong, Xiaolu; Zhou, Dongsheng; Lv, Meng; Yang, Wenhui (Frontiers in Immunology, 2022)
Anthrax caused by Bacillus anthracis is a fatal zoonotic disease with a high lethality and poor prognosis. Inhalational anthrax is the most severe of the three forms of anthrax. The currently licensed commercial human anthrax vaccines require a complex immunization procedure for efficacy and have side effects that limit its use in emergent situations. Thus, development of a better anthrax vaccine is necessary. In this study, we evaluate the potency and efficacy of aerosolized intratracheal (i.t.) inoculation with recombinant protective antigen (rPA) subunit vaccines against aerosolized B. anthracis Pasteur II spores (an attenuated strain) challenge in a B10.D2-Hc0 mouse (deficient in complement component C5) model. Immunization of rPA in liquid, powder or powder reconstituted formulations via i.t. route conferred 100% protection against a 20× LD50 aerosolized Pasteur II spore challenge in mice, compared with only 50% of s.c. injection with liquid rPA. Consistently, i.t. inoculation of rPA vaccines induced a higher lethal toxin (LeTx) neutralizing antibody titer, a stronger lung mucosal immune response and a greater cellular immune response than s.c. injection. Our results demonstrate that immunization with rPA dry powder vaccine via i.t. route may provide a stable and effective strategy to improve currently available anthrax vaccines and B10.D2-Hc0 mice challenged with B. anthracis attenuated strains might be an alternative model for anthrax vaccine candidate screening.